Impact of race and gender on antithrombotic therapy - Capodanno, Davide; Angiolillo, Dominick J. (Thrombosis and Haemostasis, 2010)
Large randomised trials support the use of a variety of antithrombotic drugs for treatment of atherothrombotic disease processes leading to cardiovascular disease. The heterogeneous case-mix of patients enrolled in these trials, however, hamper the attempt to generalise their findings to subgroups which are not sufficiently represented in the study population, such as women and ethnic minorities. Sex- and race-specific disparities in the clinical presentation, management, and outcomes of coronary artery disease may relate to underlying differences in thrombotic profiles and response to antithrombotic therapies. The present manuscript provides an overview of the currently available data on the epidemiology of coronary artery disease based on gender and race as well as the biological considerations for their differences in thrombosis and haemostasis and effects of antithrombotic therapy.
Keywords: Antithrombin; platelet pharmacology; antiplatelet agents